Caracterización y estimación de la constante cinética del cuesco de la palma de aceite en procesos de gasificación por oxidación parcial con mezcla de aire-vapor como agente oxidante (2017)
"Colombia is the fourth largest producer of oil palm in the world and the first in America, producing 1,100,000 tons of oil from the 483,733 hectares planted in 73 municipalities. The oil palm husk (CH) is about 7% of the total weight of the fruit, so this material can be used as feedstock for thermal gasification processes in order to produce liquid and gaseous fuels. This paper deals with the following topics: (1) Chemical characterization of the oil palm husk with which (2) simulations were performed with adiabatic gasification models with air-vapor mixture as oxidizing agent and (3) thermogravimetric analyzes were performed experimentally to determine the activation energy (E) of the oil palm husk. For the chemical characterization of the biomass, a proximal and elemental analysis was carried out to determine the composition of the biomass." -- Tomado del Formato de Documento de Grado.